Penanganan pandemi influenza di Jawa Timur tahun 1918-1920 - Annisa Amalia; Dewa Agung Gede Agung (Historiography: Journal of Indonesian History and Education, 2023)
This article discusses the handling of the influenza pandemic in East Java in 1918-1920. Like Covid-19, the nature of influenza is rapidly contagious so that in a short time it can infect the population until it is fatal, namely death. This raises questions about how the historical background and development of the influenza pandemic in East Java in 1918-1920, how the response of the community, doctors, health services, government and education agencies to the emergence of the influenza pandemic in East Java in 1918-1920, and how the form of handling the influenza pandemic in East Java in 1918-1920. The method used in this research uses the historical method, by searching and reading in-depth sources in archives, theses, books, and journals. This writing shows that the development of the influenza pandemic in East Java can be seen from the number of infected patients, and the death rate caused by the influenza pandemic. The influenza pandemic attack in East Java then led to responses from various parties including the health department which had denied that influenza was not dangerous, doctors and the public who experienced misinformation in their treatment, and the Surabaya government which denied the occurrence of influenza in several places. The form of handling the influenza pandemic in East Java is divided into two, namely medical and non-medical treatments.Artikel ini membahas mengenai penanganan pandemi influenza di Jawa Timur tahun 1918-1920. Seperti Covid-19 sifat penyakit influenza ini cepat menular sehingga dalam waktu singkat mampu menginfeksi penduduk hingga berakibat fatal yakni kematian. Dengan adanya hal tersebut memunculkan pertanyaan mengenai bagaimana latar sejarah dan perkembangan pandemi influenza di Jawa Timur tahun 1918-1920?, bagaimana respon dari masyarakat, dokter, dinas kesehatan, pemerintah dan dinas pendidikan terhadap munculnya pandemi influenza di Jawa Timur tahun 1918-1920?, dan bagaimana bentuk penanganan pandemi influenza di Jawa Timur tahun 1918-1920. Metode yang digunakan dalam penelitian ini menggunakan metode sejarah, dengan melakukan penelusuran dan pembacaan sumber yang mendalam dalam arsip, skripsi, buku, dan jurnal. Penulisan ini menunjukkan bahwa perkembangan pandemi influenza di Jawa Timur dapat dilihat dari jumlah pasien terinfeksi, dan angka kematian yang disebabkan oleh pandemi influenza. Adanya serangan pandemi influenza di Jawa Timur ini kemudian memunculkan respon dari berbagai pihak diantaranya dinas kesehatan yang sempat membantah bahwa influenza ini tidak berbahaya, dokter dan masyarakat yang mengalami misinformasi dalam pengobatannya, dan pemerintah Surabaja yang membantah terjadinya influenza di beberapa tempat. Bentuk penanganan pandemi influenza di Jawa Timur dibagi menjadi dua yakni penanganan secara medis dan nonmedis.